Fields of Engagement: Baseball in Rural Ontario, 1870-1925 - Robinson, Ben (Ontario History)

(untitled) (The Ontario Historical Society, 2010)
Baseball’s place in Ontario history, especially in rural areas, has been undervalued and overlooked in favor of other, more visibly Canadian pastimes such as hockey and lacrosse. But rural Ontarians have long played baseball and for a number of reasons. Their participation in baseball, through the appropriation, acceptance, and rejection of various elements of the sport, helps us define order, community structure, and identity in rural Ontario.